ARAH DAN KECEPATAN ANGIN DI KABUPATEN WAKATOBI SEBAGAI SUMBER PEMBANGKIT LISTRIK TENAGA ANGIN - Eva Safitri Maladeni; Alfian Ishak (Envirotek : Jurnal Ilmiah Teknik Lingkungan, 2021)
This study analyzes the distribution of potential areas that have wind power as a source of electrical energy. The study used a qualitative statistical and survey approach. The tools used are GPS, Anemometer, Stopwatch, GIS Application (Software), Computers and writing instruments and a camera. Data were analyzed descriptively qualitatively. Wakatobi Regency has the potential for wind to develop electrical energy, namely 5 points on Wangi-Wangi Island; 5 points on Kaledupa Island; 4 points of Tomia Island; and 4 points on Binongko Island. The wind direction on Binongko Island and Tomia Island blows from the West (W) or 280.090. On the island of Kaledupa blowing from the W (West) or 280.090. Wangi-Wangi Island blows from the NW (Northwest) or 326,030. The average wind speed in the study area shows that the average annual wind speed ranges from 4-5 m/s (minimum standard 2.5 m/s) so that Wakatobi Regency is potential for developing wind power electricity.